The Influence of Perceived Service Quality, Perceived Price Fairness, and Product Glocalization on Repurchase Intention: The Mediating Role of Customer Satisfaction - Desthia Natasya; Ahmad Shalahuddin; Bintoro Bagus Purmono; Nur Afifah; Juniwati (Journal of Educational Management Research, 2026)
This study aims to examine the influence of Perceived Service Quality, Perceived Price Fairness, and Product Glocalization on Repurchase Intention, with Customer Satisfaction serving as a mediating variable. The research employs a causal design with a quantitative approach. Data were collected through a five-point Likert-scale questionnaire administered to 288 respondents selected using purposive sampling, with criteria including a minimum age of 15 years and at least two purchases within the past three months. The data were analyzed using Covariance-Based Structural Equation Modeling (CB-SEM) with AMOS. The results indicate that Perceived Service Quality, Perceived Price Fairness, and Product Glocalization have positive and significant effects on Customer Satisfaction and Repurchase Intention. Furthermore, Customer Satisfaction significantly mediates the relationship between the three independent variables and Repurchase Intention. These findings highlight the strategic importance of enhancing service quality, ensuring price fairness, and implementing effective glocalization strategies to strengthen customer satisfaction and encourage repeat purchase behavior.